Government competition, corruption and green total factor energy efficiency: An empirical analysis from china - Zhao, Junfeng; Yan, Jinling; Yang, Xiaodong; Nie, Chunxia; Sun, Hui; Ran, Qiying (Frontiers in Environmental Science, 2022)
Currently, global warming and resource and environmental constraints are becoming formidable. Improving green total factor energy efficiency (GTFEE) is an effective tactic to alleviate carbon emissions and resource scarcity, and also a practical demand for the sustainable and healthy development of China's economy. This study applies the super efficiency SBM model to calculate GTFEE of China’s 30 provinces over the period from 2006 to 2020, and then the dynamic spatial Durbin model (SDM) is employed to investigate the impact of government competition on GTFEE. Furthermore, the influence path between government competition and GTFEE is identified by the intermediary effect model. The findings reveal that as a whole, local government competition has undermined GTFEE both in local and adjacent areas, but significant differences exist in different regions. After the robustness tests, the conclusions remain valid. The intermediary effect results show that government competition indirectly inhibits GTFEE by triggering corruption. Based on this, policymakers should establish an effective performance appraising for local governments to spark a cycle of virtuous competition and cooperation among regions. Meanwhile, the anti-corruption system should be improved so as to shape a favorable institutional atmosphere for the improvement of GTFEE, and ultimately promote the sustainable development of China's economy.